Death of a witch - Beaton, M. C. (New York : Grand Central Pub., 2009)
Hamish Macbeth, Scotland's most laconic and low-tech policeman, investigates the death of a woman with seemingly unearthly powers.
Keywords: Macbeth, Hamish -- (Fictitious character) -- Fiction; Herbalists -- Crimes against -- Fiction; Police -- Scotland -- Highlands -- Fiction; Highlands (Scotland) -- Fiction; Mystery fiction